The effect of entrepreneurial orientation, use of information technology, and innovation capability on SMEs' competitive advantage and performance: evidence from Indonesia - Shabrina Widyanti; M Mahfudz (Diponegoro International Journal of Business, 2020)
The purpose of this paper is to analyze the effect of entrepreneurial orientation, the use of information technology, and the capability of innovation on competitive advantage and performance of SMEs through competitive advantage. In this research, the sample was 125 SMEs joined in the digital class "X" in Semarang City. The result of the analysis using SEM shows that entrepreneurial orientation positively affects performance and competitive advantage of SMEs. Innovation capabilities also have a positive effect on SMEs' competitive advantage and performance. The result also suggested that use of information technology has a positive effect on the competitive advantage and competitive advantage has a positive effect on the business performance of SMEs